A novel A-D-A small molecule with 1, 8-naphthalimide as a potential non-fullerene acceptor for solution processable solar cells. (July 2017) - Zhu, Mengmeng; Miao, Jingsheng; Hu, Zhao; Chen, Yantong; Liu, Ming; Murtaza, Imran; Meng, Hong
Abstract: In this work, the structure-property relationship of fused-ring electron acceptors is briefly discussed and the principle of molecular design is presented. Based on this principle, perylene diimide (PDI) was cracked by inserting thiophene and thieno[3, 2- b ]thiophene (TT) to design and synthesize a novel A-D-A (acceptor-donor-acceptor) small molecule DNIT-TT2T, which served as a non-fullerene acceptor material in our fabricated organic solar cells (OSCs). DNIT-TT2T shows excellent thermal stability, it possesses a broad absorption by covering the wavelength range of 300–600 nm and relatively high LUMO energy level of −3.75 eV, which is close to the theoretically calculated value. The power conversion efficiency (PCE) of OSCs based on the blend of P3HT donor and DNIT-TT2T acceptor (1:1, w/w) is found to be 1.25%, with a high open-circuit voltage ( V oc ) of 0.88 V, indicating that 1, 8-naphthalimide (NI) based molecules are promising acceptors for non-fullerene polymer solar cells and excellent photovoltaic properties can be achieved by rationally designing the molecules. Graphical abstract: Highlights: The structure-property relationship of fused-ring electron acceptors is briefly discussed. The principle of molecular design is presented. A novel non-fullerene acceptor material DNIT-TT2T is designed and synthesized. OSCs based on P3HT:DNIT-TT2T are investigated, exhibiting high V oc.